Geomorphological immaturity as a factor conditioning the dynamics of channel processes in Rządza River - Bujakowski Filip (De Gruyter, 2021)
A major part of Poland, classified geographically as Polish Lowland, is covered by a layer of loose or cohesive sediments whose thickness increases toward the north. Numerous authors emphasize the impact of the protrusion of the erosional base level on the course of processes shaping modern river valleys. It has been demonstrated, among other things, that the culmination of the sub-alluvial, cohesive bedrock determines the manner in which the channel zone and the adjacent floodplain are formed, which is associated with the hydrological system of the river. A number (12) of geological documenting holes have been drilled to the bottom of the valley. Also, geological profiles were recorded for 34 natural outcrops. The range of the individual outcrops was determined using a geomorphological analysis based on, among other things, the data from airborne laser scanning. The main objective of the research based on geomorphological criteria was to identify the differences in valley morphology and geological structure as well as the dynamics of currently occurring fluvial processes, along with geological features influencing their development, in particular in the middle course of a river. The research allowed the distinction of three geologically and geomorphologically characteristic sections. This allowed an answer to the question: why is the river in the lowland similar to a mountain stream.